EFECTS OF CHEMICAL COMPOSITION ON THE MICROSTRUCTURE AND PROPERTIES OF THE CU-Ge-Sb ALLOYS - Gurešić, D.; Đorđević, A.; Marković, A.; Tomović, M.; Talijan, N.; Manasijević, I. (Journal of Engineering & Processing Management, 2016)
In the current study a ternary Cu-Ge-Sb system has been experimentally assessed. Chemical and phase compositions of the alloy samples from three vertical sections Cu-GeSb, Ge-CuSb and SbCuGe were studied using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) and confirmed by X-ray diffraction analysis (XRD). Hardness of the alloys was measured by Brinell method while hardness of phases was measured using micro Vickers method. Electrical conductivity of the studied alloys was measured using eddy current instrument. Based on experimentally determined values iso-lines of hardness and electrical conductivity for the whole ternary system were calculated using assumed mathematical models.